LOGOS : Encounter of the Divine and the Human - Simamora, Serpulus (UNIKA Santo Thomas, 2003)
â€œWhat is in a name?â€ William Shakespear wrote in his famous story Romeo and Juliet. Dragged out of its context, the saying seems to show insignificancy of a name. Is a name mere an arbitrary appellation for something or someone without any meaning inside? Before Shakespear, Cicero told us that â€œNomen est omen!â€ Name, accordingly, is sign, augury, prognostication, prediction. If itâ€™s so, a name, therefore, contains something beyond. It signifies something. In this regard I agree with Cicero, bearing in mind that a name â€œconcealsâ€ something else, be it hope, mission, essence or anything else. The Faculty of Philosophy of the Catholic University, St. Thomas â€“ Medan (Philosophical and Theological High School, St. John â€“ Pematangsiantar), picks up â€˜Logosâ€™ as the name of its scientific magazine. What is the idea lying behind this choice? To what extend does the name bear its â€˜omenâ€™? This simple article tries to deal with the question to account for the name, Logos. This presentation is a descriptive one.